Working memory capacity in children with early and late cochlear implantation: a P300 evaluation - Puri, Nishtha; Shubhadarshan, Archisman (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Cochlear Implant helps in improving hearing sensitivity, speech perception and production, cognitive abilities, and enhances academic performances, peer relationships and quality of life. Hearing impaired individuals has reduced working memory capacity and working memory depends on the ability of hearing and processing of information to the brain. P300 act as an electrophysiological test to assess the working memory capacity. The aim of the study was to evaluate the effect of age of cochlear implant on working memory capacity. Method: A total of 30 participants were included in this study, which were divided into two groups. Group 1 consisted of 15 individuals who had done cochlear implant (CI) before 3 years of age. In Group 2, 15 subjects were included who had done their CI after 3 year of age and before 6 years of age. P300 was carried out among these individuals using speech stimulus and the result was compared between groups. Result: The t test value for P300 amplitude (t:10.34, p<0.05) and latency (t:4.66, p<0.05) indicate that there are statistically significant differences exist between the two groups in terms of P300 amplitude and latency. From the mean value we can conclude that early-implanted individuals have higher amplitude and shorter latency compared to late-implanted individuals. Conclusion: The results of this study have significant ramifications for how the therapeutic strategy for kids with congenital hearing loss is planned. It highlights the need of early action and the crucial timeframe. It assesses the neuromodulation of the brain’s auditory regions directly and connects it to the implanted age.